2009
DOI: 10.1038/hr.2009.13
|View full text |Cite
|
Sign up to set email alerts
|

Silent cerebral microbleeds associated with arterial stiffness in an apparently healthy subject

Abstract: Silent cerebral microbleeds (MBs) are a common finding in stroke patients, especially those with intracerebral hemorrhage, and are thought to be a marker of future cerebral hemorrhage. Clinically, two distinct forms of MBs have been documented, those observed with either or both stroke or small vessel disease (SVD) and those associated with cerebral amyloid angiopathy. We investigated a possible association between MBs and arterial stiffness in a general population. Subjects were 443 apparently healthy individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 42 publications
2
43
1
1
Order By: Relevance
“…Several other studies have been performed in the general population investigating the association between arterial stiffness and markers of cerebral small vessel disease. 8,9,[11][12][13] Our finding that arterial stiffness is associated with WML volume is in line with these studies. 9,11,13 However, all of these studies used the brachial-ankle pulse wave velocity as a proxy for arterial stiffness.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Several other studies have been performed in the general population investigating the association between arterial stiffness and markers of cerebral small vessel disease. 8,9,[11][12][13] Our finding that arterial stiffness is associated with WML volume is in line with these studies. 9,11,13 However, all of these studies used the brachial-ankle pulse wave velocity as a proxy for arterial stiffness.…”
Section: Discussionsupporting
confidence: 82%
“…6 -15 Some previous studies furthermore suggested that arterial stiffness may be influenced differentially by blood pressure with the strongest effects in subjects with hypertension. 1,16 Most of the aforementioned studies, however, used proxy markers for arterial stiffness, including the brachial-ankle pulse wave velocity and arterial pulse waves, 8,9,[11][12][13] or were performed in selected populations with high cardiovascular risk. 6,7,10,14,15 Carotidfemoral pulse wave velocity is considered as the "gold standard" measurement of arterial stiffness and allows direct investigation of the association between arterial stiffness and small vessel disease.…”
mentioning
confidence: 99%
“…PVH was further classified into 5 grades according to a scale developed by Shinohara et al 21 and later modified and published as a guideline by the Japan Brain Dock Society, as follows: grade 0, absent or only a rim; grade 1, limited lesion-like caps; grade 2, irregular halo; grade 3, irregular margins and extension into the deep white matter; and grade 4, extension into the deep white matter and subcortical portion. PVH grade ≥2 was considered a pathological condition according to the guideline, as well as based on our previous findings indicating a greater frequency of left ventricular hypertrophy 22 and microbleeds 23 in subjects showing PVH grade ≥2 than in those with lower scores. Imaging analysis was performed by neurologists without clinical information on the subject.…”
Section: Mri and Assessment Of Silent Cerebral Damagementioning
confidence: 99%
“…Our results were partially in line with the previous findings of a close association between the PWV and CMBs. [14][15][16] However, the PWV is affected by changes in blood pressure during measurement and might not accurately reflect atherosclerosis in hypertensive patients. 8 In contrast, the CAVI is less influenced by blood pressure during measurement than is the PWV.…”
Section: Discussionmentioning
confidence: 99%